Mapping the landscape of small-sided games in team sports: A bibliometric analysis and literature review - Endriani, Dewi; Gultom, Syamsul; Fahmi, Mhd; Destya, Muhammad Reza; Nadzalan, Ali bin Md (UIR Press, 2024)
Background Problems: Small-sided games (SSGs) have become a significant focus of research in the context of team sports, and a thorough review and analysis of the existing research landscape is needed to identify trends, gaps, and emerging themes. Research Objectives: This study aims to map the research landscape on small-sided games (SSGs) in the context of team sports through a bibliometric approach and a literature review. Methods: Literature was drawn from established research sources in the Scopus and Web of Science databases from 2014 to 2023. The final data used for this study consisted of 1012 articles, which were then analysed using a bibliometric approach, and the literature review was limited to 237 articles after grouping ten types of team sports using the ScientoPy tool. Findings and Results: The results showed a consistent increase in interest in SSGs, with journals such as “Journal of Strength and Conditioning Research” and “Biology of Sport” playing an important role in expanding understanding of the topic. The analysis also revealed that authors such as Clemente F.M. and Praca G.M. had a significant impact on developing knowledge about SSGs. Although football dominated the related literature, the results also highlighted other sports such as basketball, futsal, and handball. However, there is still a lack of SSG research for sports such as cricket and dodgeball. The benefits of SSGs in team sports include improved technical skills, physical fitness, tactical understanding, and physical performance. Conclusion: This study provides insight into the important role of SSGs in athlete development and team sports training and highlights the need for further research to optimise the full potential of this training method.